Strengthening Ideological Values through Pasantian Singing: Problematizing the Nexus Between Local Cultural Practices and Globality in Bali - I Komang Sudirga; Made Mantle Hood; Ni Ketut Dewi Yulianti (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This article aims to explore the traditional cultural practices of pasantian reading clubs in facing globality and subjective perceptions of modernity, transformation and change. Pasantian members sing and interpret conventional Balinese texts, thus playing a crucial role in maintaining the artistic and ideological identity of Bali Hindu people. However, engagement in these practices is significantly challenged by rapid sociological changes, which have led to a notable decline in the number of people involved in pasantian. The study focused on understanding how pasantian interact with notions of globality and how these groups can be strengthened to preserve local cultural and ideological values. A qualitative approach employed ethnographic methods such as participant observation and in-depth interviews to explore the practices of pasantian in terms of continuity and change. Findings highlight the importance of practitioners of traditional art forms in negotiating the local-global nexus and suggest strategies for revitalizing pasantian groups.